Producing starch-based bioplastic from durian skin with the addition of sorbitol plasticizer and chitosan filler - Rahmatullah Rahmatullah; Rizka Wulandari Putri; Rifqi Sufra (Chemical Engineering Department, Faculty of Engineering, Universitas Sriwijaya in collaboration with Asosiasi Pendidikan Tinggi Teknik Kimia Indonesia (APTEKIM), 2024)
Plastic and organic waste are global issues in various developing countries, especially Indonesia.Unproper waste management will bring a negative impact on the environment. Organic waste such as durian skin can be converted into starch as a raw material for bioplastics as an alternative solution to reduce plastic waste. This study aims to make bioplastics based on starch from durian skin with the addition of sorbitol as a plasticizer and chitosan as a filler with the addition of tapioca flour adhesive. The ratio of tapioca flour to durian skin starch is 2:0.75, 2:1, 2:2, while the concentration of sorbitol plasticizer used is 25 %, and chitosan filler is 4 % of the total starch mass. The samples were characterized by physical and mechanical tests (thickness, tensile strength, elongation, and young's modulus), functional group tests with FTIR, and thermal strength tests with TGA-DTG. From the results, the best sample was sample C (the ratio of tapioca flour to durian skin starch 2:2, sorbitol plasticizer 3.00 ml, and chitosan filler 0.48 g) with a thickness of 0.11 mm, tensile strength 31.44 MPa, young's modulus 31.23 MPa, and stable thermal resistance with the smallest mass loss of 81.454 % up to a temperature of 600 oC.